Correction: A spiropyran–coumarin platform: an environment sensitive photoresponsive drug delivery system for efficient cancer therapy. Issue 24 (1st June 2017) - Barman, Shrabani; Das, Joyjyoti; Biswas, Sandipan; Maiti, T. K.; Pradeep Singh, N. D.
Abstract : Correction for 'A spiropyran–coumarin platform: an environment sensitive photoresponsive drug delivery system for efficient cancer therapy' by Shrabani Barman et al., J. Mater. Chem. B, 2017, DOI: 10.1039/c7tb00379j.